2017
DOI: 10.3390/ijms18061282
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effect of Metformin on Postprandial Hypertriglyceridemia through Delayed Gastric Emptying

Abstract: Postprandial hypertriglyceridemia is a potential target for cardiovascular disease prevention in patients with diabetic dyslipidemia. Metformin has been reported to reduce plasma triglyceride concentrations in the postprandial states. However, little is known about the mechanisms underlying the triglyceride-lowering effect of metformin. Here, we examined the effects of metformin on lipid metabolism after olive oil-loading in 129S mice fed a high fat diet for three weeks. Metformin administration (250 mg/kg) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
(35 reference statements)
1
12
1
Order By: Relevance
“…In particular, participants with a larger reduction in AUC 0–4 h for glucose showed larger effects on AUC 0–4 h for TG. These findings are in agreement with those of our previous pre‐clinical study in which pre‐Met administration lowered plasma TG and glucose levels in mice. Furthermore, the present findings are consistent with a previous clinical study that showed lower glucose concentrations with pre‐Met administration before oral glucose tolerance testing.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In particular, participants with a larger reduction in AUC 0–4 h for glucose showed larger effects on AUC 0–4 h for TG. These findings are in agreement with those of our previous pre‐clinical study in which pre‐Met administration lowered plasma TG and glucose levels in mice. Furthermore, the present findings are consistent with a previous clinical study that showed lower glucose concentrations with pre‐Met administration before oral glucose tolerance testing.…”
Section: Discussionsupporting
confidence: 94%
“…This effect, similar to its glucose‐lowering effect, was reported to be dose‐dependent. Recently, we found that the administration of high‐dose metformin before fat loading significantly reduced postprandial plasma TG levels compared with administration after fat loading in an animal model. We therefore concluded that the major mechanism underlying the TG‐lowering effect of metformin is a reduction in intestinal absorption through delayed gastric emptying, and not an increase in fat oxidation in the peripheral tissues.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Although both groups can be considered to be well controlled with regard to glucose homeostasis, it is conceivable that the difference may have resulted in discretely different lipid metabolism before treatment initiation; however, this did not translate into different effects of metformin treatment on lipid metabolism at the end of the study. Third, it is possible that metformin may affect postprandial and not postabsorptive lipid metabolism as suggested by other groups . Exploring this possibility will require a completely different experimental setup.…”
Section: Discussionmentioning
confidence: 97%
“…Despite reports from previous studies showing that postprandial glucose decreased due to delayed gastric emptying 45,46 , the relationship between delayed gastric emptying and decreased postprandial TG was unknown until recently. Sato et al reported that the TG-lowering effect of metformin was mediated by delayed gastric emptying for the first time 47 . In the present study, fasting ghrelin level was extremely correlated with the postprandial TG response, such that the TG-lowering effect of BL was remarkable in subjects with high fasting ghrelin.…”
Section: Discussionmentioning
confidence: 99%